PERAN AJARAN NITISASTRA DALAM PEMBENTUKAN PENDIDIKAN KARAKTER GENERASI MUDA BANGSA - Ni Kadek Chandra Putri Irani (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
The young generation is the successor of the nation who has a stake in determining the future and integrity of the Indonesian nation. Therefore, the importance of fostering character education for the younger generation must be instilled early considering immoral cases are increasingly rife with society. In connection with the alignment of the basic values of character education with the values contained in the teachings of Hinduism, character formation can be echoed based on the concept of Nitisastra leadership in the teachings of Hinduism. The value of character education that can be realized is religious, social care, responsibility, peace of mind, hard work, democracy and discipline. Key Word : Nitisastra, Character Education, Young Generation